2022
DOI: 10.20944/preprints202201.0076.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assembly and Disassembly Mechanics of a Cylindrical Snap Fit

Abstract: Snap fit is a common mechanical mechanism. It uses the physical asymmetry that is easy to assemble but difficult to disassemble to provide a simple and fast link between objects. The ingenious combination of geometric shape, bending elasticity and friction of the snap fit is the mechanism behind the easy to assemble but difficult to disassemble disassemble. Yoshida and Wada (2020) has done a groundbreaking work in the analysis of the elastic snap fit. During our study of their paper, while we really enjoyed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…By data fitting, the correction coefficient is determined approximately as C = 2.95. Since the coefficient C should be greater than 1, it indicates that the spherical snap fit has a greater bearing capacity than the cylindrical snap fit [12,13], confirming our prediction in the preface. Eq.…”
Section: Mechanical Fitting Theory Of Assembly and Disassembly Of Sin...supporting
confidence: 83%
See 4 more Smart Citations
“…By data fitting, the correction coefficient is determined approximately as C = 2.95. Since the coefficient C should be greater than 1, it indicates that the spherical snap fit has a greater bearing capacity than the cylindrical snap fit [12,13], confirming our prediction in the preface. Eq.…”
Section: Mechanical Fitting Theory Of Assembly and Disassembly Of Sin...supporting
confidence: 83%
“…Taking the spherical snap fit with two pairs of claws as an example, we use finite element method to study the assembly and disassembly mechanism of multi-jaw spherical snap fit, as shown in Fig. (13). We take the opening angle of Type I snap-fit φ = 2.3 rad and Type II snapfit φ = 2.7 rad as examples, and the simulation process is the same as above.…”
Section: Fig 12: Multi-jaw Spherical Snap Fitmentioning
confidence: 99%
See 3 more Smart Citations